Hydroethanolic extract of Juglans regia L. green husks: A source of bioactive phytochemicals - Vieira, Vanessa (2018)
Juglans regia L. (walnut) green husks are an important fraction of waste resulting from the walnut production, thus representing an interesting natural matrix to explore as a source of bioactive compounds. In this work, the hydroethanolic extract of walnut green husks was studied considering the phytochemical composition and the biological activity using different cell model assays, most of them evaluated for the first time for this matrix. From the HPLC-DAD-ESI/MSn analysis, sixteen compounds were identified, being the extract mostly composed of naphthalene derivatives (including tetralone derivatives) and less abundant in phenolic compounds (hydroxycinnamic acids and flavonols). The cytotoxic potential of the extract was assessed against tumour (MCF- 7, NCI–H460, HeLa and HepG2) and non-tumour (PLP2) cell lines. Moreover, the antioxidant activity of the extract was evaluated by inhibition of the oxidative haemolysis (OxHLIA) and the formation of thiobarbituric acid reactive substances (TBARS), and the anti-inflammatory potential by the inhibition of the NO production by the RAW264.7 cell culture. The antibacterial effects of the extract were also evaluated against Gram-negative and Gram-positive bacteria. The results obtained represent a stepping stone for the development of future applications using walnut green husks as a source of added value compounds with bioactive potential.